RF-Characterization of HZO Thin Film Varactors - Sukhrob Abdulazhanov, Quang Huy Le, Dang Khoa Huynh, Defu Wang, Maximilian Lederer, Ricardo Olivo, Konstantin Mertens, Jennifer (Crystals, 2021)
A microwave characterization at UHF band of a ferroelectric hafnium zirconium oxide metal-ferroelectric-metal (MFM) capacitors for varactor applications has been performed. By using an impedance reflectivity method, a complex dielectric permittivity was obtained at frequencies up to 500 MHz. Ferroelectric Hf0.5Zr0.5O2 of 10 nm thickness has demonstrated a stable permittivity switching in the whole frequency range. A constant increase of the calculated dielectric loss is observed, which is shown to be an effect of electric field distribution on highly resistive titanium nitride (TiN) thin film electrodes. The C-V characteristics of a “butterfly” shape was also extracted, where the varactors exhibited a reduction of capacitance tunability from 18.6% at 10 MHz to 15.4% at 500 MHz.